Embracing Complexity and Decentralization in Organizations : an Operational Approach. - LePore, Domenico (Business Expert Press, 1919)
Our world is increasingly digital and decentralized. We must therefore urgently rethink, structurally and operationally, how organizations are designed so they can adapt and compete in the digital age. This starts by understanding the problems raised by complexity. Managing an organization as a network entails forgoing a command and control management style but at the same time requires a powerful mechanism to ensure that activities are properly coordinated and every-body in the network is accountable. We can find a suitable organizational structure if we look at the fundamental elements that make up the work of an organization. Just as the key constituents of life are hydrogen, oxygen, carbon, nitrogen, phosphorus, and sulfur, we can say that the basic constituents of work are repetitive processes and one-off projects.